Factors associated with Catastrophic Healthcare Expenditure in communities of Lagos Nigeria: A Megacity experience - Kikelomo Ololade Wright; Adeyinka Adeniran; Adedayo Aderibigbe; Olufunsho Akinyemi; Temiloluwa Fagbemi; Omoyeni Ayodeji; Biola Adepase; Emmanuella Zamba; Hussein Abdurrazzaq; Faith Oniyire; Olusegun Ogboye; Akin Abayomi (PLoS ONE, 2025)
Background Each year, millions of people in low—and middle-income countries such as Nigeria are forced into poverty and financial ruin due to out-of-pocket (OOP) healthcare expenses. Our study assessed the prevalence and determinants of Catastrophic Healthcare Expenditure (CHE) experienced by households in Lagos, Nigeria. Methods A descriptive community-based cross-sectional survey was conducted on 2492 households in Lagos from December 2022 to March 2023 in 4 Local Government Areas (LGAs) using a multistage sampling technique. Data was collected using pre-tested semi-structured questionnaires, and analysis was performed using STATA 15.0 software. Univariate, bivariate, and binary logistic regression analyses were conducted with statistical significance set at p<0.05, and a 95% Confidence Interval was calculated for the adjusted odds ratio (OR). Results The study revealed that 15% of households experience catastrophic health expenditure (CHE). Gender, marital status, educational level, occupation, personal income, health perception, household location, and health insurance enrollment were significantly associated with CHE. Additionally, gender, religion, income, household location, and self-rated health status were significant predictors of household CHE, with adjusted odds ratios of 4.42, 2.45, 1.00, 1.07, and 1.69, respectively. Conclusion CHE is more prevalent among people with lower socio-economic status, urban residents, and those lacking health insurance. It is crucial to implement targeted initiatives to raise awareness about the benefits of health insurance and simplify the enrollment process for vulnerable groups, thereby alleviating the financial strain of healthcare expenses.